THE PHONETIC PHENOMENON OF REDUCTION IN ENGLISH - Khaydarova Nigora,; Sotvoldieva Nozimakhon, (TADQIQOTLAR, 2025)
Abstract  this  article  discusses  the  phonetic  phenomenon  of  reduction  in  the English  language,  its  types,  causes,  and  importance  in  speech.  Reduction  plays  a significant role in the natural flow of spoken English and contributes to the rhythm and melody of the language.